Analisis Perbandingan Kelayakan Usahatani Jeruk Siam dan Jeruk Kintamani Di Desa Manikliyu, Kecamatan Kintamani, Kabupaten Bangli - SETIAWAN, MAULIKA NURUL ANNISA; SUDARMA, I MADE; DJELANTIK, AAA WULANDIRA SAWITRI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Feasibility Analysis of Siam Oranges and Kintamani Oranges Farming in Manikliyu Village, Kintamani District, Bangli Regency Orange plants are one of the plants that are widely cultivated by farmers in Kintamani District. This study aims to compare the income between Siamese orange and Kintamani orange farming using investment feasibility criteria. The data used in the form of quantitative data. The data obtained from from direct interviews with the number of respondents 20 farmers. This research was conducted using quantitative descriptive analysis method. The results of the analysis show that Siamese orange farming is more profitable than Kitamani oranges based on the investment criteria, with a B-C ratio of Siamese oranges of 1.63, kintamani oranges by 1.26. NPV of Siamese oranges Rp2,908,740,114.75; kintamani oranges Rp.1,243,369,105,82 and the IRR of Siamese oranges is 19.97%; kintamani oranges 15.75%. Payback Period Siamese oranges for 7 years 6 months; kintamani oranges at 8 years and 1 month with the economic age of 10 years. The results of the sensitivity analysis showed that Siamese orange farming and Kintamani orange farming were not sensitive to changes in costs up 5%, 10% and income decreased by 10%. However, from the results of this study, it is recommended that farmers continue farming Siamese oranges rather than kintamani oranges because it provides higher income.